Awareness on green hotel environmental management system (EMS) practices and revisit intention / Izwan Hadi Mohamed Abdullah - Mohamed Abdullah, Izwan Hadi (2013)
With the escalation over environment concern, more hotels had started to engage with environmental practices. Various studies later paid their attention on the EMS implementation in the hotel settings. Despite huge emphasis made on literature pertaining the EMS, little has been known of its impacts from the perspectives of the end users. This study wants to fill this research gap. Therefore, this paper attempted to discover the EMS awareness of green customers and its relation towards intention to revisit. A total of 270 cases were gathered from three certified green hotels in Kuala Lumpur. Research findings reveal that customer’s awareness on EMS practiced by the hotel does have an impact towards their intention to revisit with full mediation effect of green satisfaction is found. New framework is proposed aligning with study result. The implication and limitation of this study are presented and discussed.